The development of language proficiency through global skills enhancement using web 2.0 tools in university EFL contexts: a mixed methods quasi-experimental study - Al-khresheh, Mohammad Hamad; Orak, Suheyla Demirkol; Alruwaili, Shatha F. (Springernature, 2025)
This mixed-methods quasi-experimental study investigates the integration of Web 2.0 tools into university EFL curricula, assessing their impact on language proficiency and global skills development. Conducted at a Turkish university with 41 international students, the study divided participants into control and experimental groups, with the latter engaging with blogs, wikis, and multimedia platforms over a 14-week term. Data were collected through standardized language proficiency tests, pre- and post-interviews, reflection journals, and instructor feedback. Quantitative analysis revealed significant language proficiency improvements in the experimental group, particularly in listening, reading, oral communication, and writing, compared to the control group. Correlation analysis confirmed that gains in global skills directly contributed to language improvements. Qualitative feedback indicated increased engagement and motivation in activities using Web 2.0. The findings suggest that authentically integrated Web 2.0 tools transform learning environments into interactive processes while promoting global skills and effectively enhancing learners' language proficiency. This study confirms the benefits of integrating Web 2.0 tools in EFL curricula, aligning educational outcomes with global workforce demands, and reveals the need for further research into long-term impacts. This affirms the significance of digital technologies in preparing students for a globalized environment, reinforcing their dual advantages in enhancing global competencies and language proficiency.
Keywords: Students; Technologies; English